2018
DOI: 10.1002/mbo3.715
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of Methanothermobacter thermautotrophicus reveals methane formation from H2 and CO2 under different temperature conditions

Abstract: The growth of all methanogens is limited to a specific temperature range. However, Methanothermobacter thermautotrophicus can be found in a variety of natural and artificial environments, the temperatures of which sometimes even exceed the temperature growth ranges of thermophiles. As a result, the extent to which methane production and survival are affected by temperature remains unclear. To investigate the mechanisms of methanogenesis that Archaea have evolved to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…This confirmed that most of these are not upregulated upon continuous growth at high temperature (for full details see Text S5, Supporting Information). This is not surprising in itself as the heat shock response is rapid but transient . Among the few proteins that are strongly affected by growth temperature is the adjacently encoded gene pair HVO_O450 and HVO_O451, both members of the Hsp20‐type heat shock protein family (also known as short Heat Shock Proteins, sHSPs).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirmed that most of these are not upregulated upon continuous growth at high temperature (for full details see Text S5, Supporting Information). This is not surprising in itself as the heat shock response is rapid but transient . Among the few proteins that are strongly affected by growth temperature is the adjacently encoded gene pair HVO_O450 and HVO_O451, both members of the Hsp20‐type heat shock protein family (also known as short Heat Shock Proteins, sHSPs).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, spectral counting, differential isotopic labelling strategies as well as label‐free quantitation were employed to study oxidative stress, the impact of individual mutations, or the exponential‐stationary growth phase transition, respectively, in Haloferax . Additional publications cover topics at the intersection of proteomics and the stress response for other archaea …”
Section: Introductionmentioning
confidence: 99%
“…CH 4 produced from the anoxic zone of paddy soils by methanogenic archaea is transported into the rice via the aerenchyma tissues in the rhizomes, roots and stems [ 56 , 57 ]. The rice tissues provide a microenvironment full of inorganic and organic substances, including C1 compounds such as methane, which allows the growth of methanotrophy bacteria that utilize CH 4 and methanol as carbon sources [ 20 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, our understanding of archaeal cell biology is lacking behind eukaryotes and bacteria. Recently, the importance of proteomics as a tool for addressing specific biological questions in archaea has become readily apparent [3][4][5][6][7][8][9][10][11][12][13] . However, such limited analyses typically leave valuable information buried in the raw data.…”
mentioning
confidence: 99%